Polycystic Liver Disease: A Case Report - Randy Adiwinata; Natalin Allorerung; Jonathan Arifputra; Andrea Livina; Pearla Lasut; Bradley Jimmy Waleleng; Fandy Gosal; Luciana Rotty; Jeanne Winarta; Andrew Waleleng; Michael Tendean (The Indonesian Society for Digestive Endoscopy, 2021)
Polycystic liver disease is characterized by multiple cystic lesions on the liver. Liver cysts are typically incidental findings, with occasional complications including cyst hemorrhage, infection and rupture. Polycystic liver disease may be part of autosomal dominant polycystic liver disease (ADPLD). Autosomal dominant polycystic liver disease is considered rare autosomal dominant disease, with prevalence of 1/100,000-1,000,000. Without family history of polycystic liver disease, ADPLD is defined as the presence of more than 20 liver cysts with no renal cysts, however up to third of ADPLD may have small number of renal cysts without kidney function impairment. This case of a 73-year-old woman with symptomatic polycystic liver disease, and we performed cyst fenestration-deroofing via laparoscopic.